2010
DOI: 10.1080/10410230903265938
|View full text |Cite
|
Sign up to set email alerts
|

Tanning, Skin Cancer Risk, and Prevention: A Content Analysis of Eight Popular Magazines That Target Female Readers, 1997–2006

Abstract: The majority of tanning bed users in the U.S. are women. Previous health communication research frequently focused on the risk of skin cancer, but few studies assessed the mediated communication environment that may surround women’s beliefs and behaviors relevant to tanning. A content analysis of articles in eight magazines targeting girls, young women, older women, and women who are interested in fitness during the ten-year period of 1997–2006 was conducted. The amount of coverage of tanning bed use consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 34 publications
0
32
0
1
Order By: Relevance
“…Stryker, Solky, and Emmons (2005) found that using sunscreen was the most frequently presented skin cancer prevention method in the content of newspaper coverage related to skin cancer from 1979 to 2003. Cho, Hall, Kosmoski, Fox, and Mastin (2010) examined eight magazines geared toward girls, women, and those specifically interested in fitness and found that 55% of articles that mentioned skin cancer prevention focused on sunscreen use; other types of prevention methods were seldom mentioned.…”
Section: Previous Studies Of Media Content Related To Sunscreen Usementioning
confidence: 98%
See 2 more Smart Citations
“…Stryker, Solky, and Emmons (2005) found that using sunscreen was the most frequently presented skin cancer prevention method in the content of newspaper coverage related to skin cancer from 1979 to 2003. Cho, Hall, Kosmoski, Fox, and Mastin (2010) examined eight magazines geared toward girls, women, and those specifically interested in fitness and found that 55% of articles that mentioned skin cancer prevention focused on sunscreen use; other types of prevention methods were seldom mentioned.…”
Section: Previous Studies Of Media Content Related To Sunscreen Usementioning
confidence: 98%
“…Eight items were included as possible benefits in accordance with the Cho et al (2010) methods: beauty benefits for skin (e.g., makes skin smoother, softer, etc. ), benefits for tanning (e.g., tan faster, tan lasts longer, etc.…”
Section: Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though its systematic review of intervention research for sun protection identified effective strategies to improve sunscreen use (38), the Task Force did not issue any sunscreen-specific recommendations on the basis that sunscreen alone was inadequate for sun protection. Regardless of the inconsistency by national groups in their sun protection recommendations, the media emphasizes sunscreen as the preferred approach to sun protection (39,40). The dominance of sunscreen more than other sun protection strategies in the media is undoubtedly reinforced by the advertising expenditures for sunscreen by the skin care industry, estimated to be US $75 million in 2011 (41).…”
Section: Disagreement About Skin Cancer Prevention Recommendationsmentioning
confidence: 99%
“…Despite the current widespread knowledge regarding skin cancer etiology, media representations of tanning have continued to be primarily positive. For example, an analysis of articles in eight American magazines targeting girls and women from 1997 to 2006 found that the amount of coverage of negative consequences of indoor tanning was less than 50% of the amount of coverage of tanning benefits (Cho et al, 2010). Indoor tanning is now a $5 billion per year industry in the US with more than 40,000 indoor tanning establishments (Looking Fit, 2009-2010.…”
Section: Current Americamentioning
confidence: 99%